Análise da governança sob a ótica dos gestores em uma Instituição Federal de Ensino Superior segundo as diretrizes do Tribunal de Contas da União: um estudo na UFTM. - Daibert, Adriana Maria Freire (2021)
The great demand of diverse needs to be met on behalf of society in face of the few resources available are daily challenges that public managers face; so, to make the process more effective, administrative models in public administration undergo constant reformulation, and public governance is currently shown as the ideal paradigm to achieve good results. In this scenario, public universities, as bodies of great relevance in the social context, must adapt to better achieve their institutional objectives; so, this research aimed to assess the view of managers of the UFTM's internal governance bodies on university governance. In accordance with the guidelines drawn up by the TCU, the body that has disseminated the culture of governance throughout the country, through studies and works related to the subject. The research used the mixed methods approach, being descriptive, of applied nature, using the case study, with content analysis by the technique of categorical analysis and simple descriptive statistics. Individual interviews, indirect observation and document analysis were used as sources. The results seem to indicate that the managers' view is compatible with what was identified by the TCU in the IGG, with low assimilation of the subject, even though good governance practices have been implemented at the university, highlighting those related to the principles of transparency and accountability, however, with improvements in planning, people management, risk management and IT processes.